Disaster Mitigation Based on Environmental of Coastal Area Communities in Pariaman City Indonesia - Oktorie, Olivia; Rusdi, Rusdi; Heldi, Heldi; Barlian, Eri; Putra, Aprizon; Ramadhan, Riski (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
Pariaman city is one of the areas most severely affected by natural disasters that have the potential for tsunamis. The impact of the earthquake potential tsunami seen in fatalities and damage to infrastructure, both residents' homes and other public facilities. The impact also caused the community to lose their livelihood. Most of the people of Nagari Gunung Padang have livelihoods as farmers, after the earthquake disaster has the potential of a tsunami, many people lost their land and gardens because of the cliff ruins and buried by landslides that caused the land cannot be recycled. By taking into account all the physical, social, and economic aspects, this is the reason for the researchers' interest to conduct research related to the direction of Natural Disaster Mitigation Policy based on Environmental Physical Conditions and Socio-Economic Characteristics of Coastal Area Communities in Pariaman city. With Mixed Method methods, such as simultaneous and sequential data collection. Then descriptive physical environmental conditions and socio-economic characteristics, and Focus Group Discussion (FGD) in policy direction. The results of this study in the form of an explanation of the physical, social and economic Pariaman city, as well as the policies needed in disaster mitigation in Pariaman city